Cartoon Images on E-juice Labels: A Descriptive Analysis. Issue 10 (30th January 2020) - Seitz, Christopher M; Orsini, Muhsin Michael; Jung, Grace; Butler, Kate
Abstract: Introduction: Although previous studies have found cartoons in electronic cigarette (e-cigarette) advertisements, social media posts, and a small sample of labels, there has yet to be an analysis of cartoons located on the labels attached to bottles of e-juice (the solution that contains nicotine and other chemicals). As such, the objective of this study was to analyze the prevalence and types of cartoons on e-juice labels. Methods: Two researchers independently analyzed the presence and types of cartoons on the labels of e-juice flavors available on eliquid.com. Based on the Master Settlement Agreement's definition of a cartoon, the cartoons were placed into five categories: (1) comically exaggerated people, (2) comically exaggerated animals, (3) comically exaggerated creatures, (4) anthropomorphic creatures, or (5) extra-human creatures. Results: There was a total of 1587 brands that offered 7135 e-juice products. Of those, 311 brands (19%) offered 1359 products (19%) that contained cartoons on the e-juice labels. From the labels that contained cartoons, 790 (58%) were of comically exaggerated people, 247 (18%) were of anthropomorphic creatures, 212 (16%) were of comically exaggerated animals, 73 (5%) were of comically exaggerated creatures, and 37 (3%) were of extra-human creatures Conclusions: Given the previous success of Joe Camel on youth tobacco use, the prevalence of cartoon images found in this study is noteworthy. In addition, the number of brands that had cartoons on e-juice labels indicates that this issue is pervasive among businesses that sell e-juice. Implications: This study adds to the body of knowledge on this topic by describing a concerning number of cartoons located on e-juice labels, indicating a need for policy that prohibits the use of cartoon images in e-cigarette packaging.